TRAVEL WRITING SEBAGAI INOVASI PENDIDIKAN PADA NOVEL ETNOGRAFI MANUSIA LANGIT KARYA J.A. SONJAYA - Dina Purnama Sari (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
This research aimed to describe the travel writing’s as an education innovation on ethnographic novel Manusia Langit by J.A. Sonjaya. This research used the method of descriptive research with structuralism approach and anthropological approach to literature relating to the intrinsic elements, travel writing, and culture. The object is an ethnographic novel Manusia Langit by J.A. Sonjaya. The conclusion is an intrinsic element in the structuralist approach has relation with culture, especially the social system; social anthropology approaches has relation with the principle of life and death, pride, party, and women, both the similarities and differences have linkage of these principles; and travel writing is an educational innovation because it can attract interest in reading, travel, and scientifics. It can be packaged in the novel.Keywords: ethnographic, anthropological literature, structuralism, academic innovation, travel writing